Penerapan Algoritma Tunstall Code Untuk Mengkompresi File Teks - Fitri, Juli; Nasution, Surya Darma; Hutabarat, Sumiaty (STMIK Budi Darma, 2021)
Text generally contains a series of characters and can form a word, letter and narrative. For example, a text file that is large in size results in the sending process taking longer, and uses a large amount of memory space in its storage. So to save storage space and speed up the process of sending text files, it is necessary to do a compression process so that the text file size becomes smaller. One of the file compression techniques that can compress text files well is file compression using the Tunstall code algorithm. The Tunstall code algorithm work system is to determine the sequence of symbols for each codeword, take the highest probability and iterate as many as N (number of symbols) to be compressed. By using the Tunstall code algorithm, the authors managed to compress a text file quite well, namely compressing the text file size from 80 bits to 40 bits with a compression ratio of 50% reduction in size.